2020
DOI: 10.1161/atvbaha.119.313359
|View full text |Cite
|
Sign up to set email alerts
|

Novel Long Noncoding RNA, Macrophage Inflammation-Suppressing Transcript ( MIST ), Regulates Macrophage Activation During Obesity

Abstract: Objective: Systemic low-grade inflammation associated with obesity and metabolic syndrome is a strong risk factor for the development of diabetes mellitus and associated cardiovascular complications. This inflammatory state is caused by release of proinflammatory cytokines by macrophages, especially in adipose tissue. Long noncoding RNAs regulate macrophage activation and inflammatory gene networks, but their role in macrophage dysfunction during diet-induced obesity has been largely unexplored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…In another example, pyroptosis, a process involving activation of the inflammasome, is controlled by the lncRNA NEAT1 in diabetic nephropathy through the action of the mir34c/NLRP3 axis ( 73 ). Most recently, a novel lncRNA, macrophage inflammation-suppressing transcript ( 74 ) has been described which is lost in obese mice and is reduced in ATM from obese patients ( 75 ). In sum, visceral AT and its complement of inflammatory cells, especially ATMs, is a highly dynamic cellular structure under a wide variety of intrinsic and extrinsic epigenetic controls.…”
Section: Insulin Resistance Inflammation and Diabetesmentioning
confidence: 99%
“…In another example, pyroptosis, a process involving activation of the inflammasome, is controlled by the lncRNA NEAT1 in diabetic nephropathy through the action of the mir34c/NLRP3 axis ( 73 ). Most recently, a novel lncRNA, macrophage inflammation-suppressing transcript ( 74 ) has been described which is lost in obese mice and is reduced in ATM from obese patients ( 75 ). In sum, visceral AT and its complement of inflammatory cells, especially ATMs, is a highly dynamic cellular structure under a wide variety of intrinsic and extrinsic epigenetic controls.…”
Section: Insulin Resistance Inflammation and Diabetesmentioning
confidence: 99%
“…Arterial inflammation occurs very early in atherogenesis and is associated with impairment of many salutary functions of the healthy endothelium. Accumulating studies point to lncRNAs as regulators of endothelial homeostasis, smooth muscle cell contractility, and macrophage-mediated inflammation in the vessel wall (11,13,(15)(16)(17)(18). This study provides evidence for the first time to our knowledge that the mouse-specific lncRNA VINAS and its human ortholog, DEPDC4, play important roles in vascular inflammation and atherogenesis.…”
Section: Discussionmentioning
confidence: 63%
“…These studies have found several novel lncRNAs enriched in macrophages and differentially expressed in diet-induced mice models with obesity and early diabetes. For example, Stapleton et al (2020) found that MIST was associated with a macrophage anti-inflammatory phenotype during gain- and loss-of-function experiments. When transcription or interaction with RNAs of MIST was disrupted, expression of inflammatory genes heavily increased.…”
Section: The Potential Of Lncrnas As Therapeutic Targets Of Related Diseases Induced By Adipocyte Dysfunctionmentioning
confidence: 99%